2006
DOI: 10.1089/ten.2006.12.3075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tissue-Engineered Vascular Autografts

Abstract: This study evaluated the endothelial function and mechanical properties of tissue-engineered vascular autografts (TEVAs) constructed with autologous mononuclear bone marrow cells (MN-BMCs) and a biodegradable scaffold using a canine inferior vena cava (IVC) model. MN-BMCs were obtained from a dog and seeded onto a biodegradable tubular scaffold consisting of polyglycolide fiber and poly(L-lactide-co-epsilon-caprolactone) sponge. This scaffold was implanted in the IVC of the same dog on the day of surgery. TEVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…Endothelial function is one of the important targets when evaluating the effects and outcomes of these experimental and clinical studies. [1][2][3] Endothelial dysfunction is associated with the development of various cardiovascular diseases and is important in atherosclerotic lesion formation and progression. [4][5][6] Thus, much effort has been devoted to understanding the molecular pathways regulating endothelial function after innovative therapies and developing strategies to improve endothelial function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial function is one of the important targets when evaluating the effects and outcomes of these experimental and clinical studies. [1][2][3] Endothelial dysfunction is associated with the development of various cardiovascular diseases and is important in atherosclerotic lesion formation and progression. [4][5][6] Thus, much effort has been devoted to understanding the molecular pathways regulating endothelial function after innovative therapies and developing strategies to improve endothelial function.…”
mentioning
confidence: 99%
“…[4][5][6] Thus, much effort has been devoted to understanding the molecular pathways regulating endothelial function after innovative therapies and developing strategies to improve endothelial function. [1][2][3] By taking advantage of gene-manipulation techniques in mice to produce various genetic modifications and avoid the rejection of xenologous cells, substantial progress has been made in cell therapy strategies and gene-introduced and cytokine-introduced angiogenesis. 7-12 Those advances produced various targets that can be used to evaluate the effects of specific therapies on endothelial function, for example, of hind limbs after experimental creation of critical ischemia.…”
mentioning
confidence: 99%
“…The techniques might be exposed to contamination. To overcome these disadvantages of cultured and clinical trials [18,19]. The application of the scaffolds was restricted to lowpressured vessels such as the pulmonary artery or vena cava because of insufficient mechanical strength.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that sponge-type PLCL scaffolds were fabricated as an artificial blood vessel by an extrusion-particulate leaching technique or a freezing-drying method [11]. Sponge-type PLCL scaffolds were limited in mechanical strength [4], while PLCL scaffolds reinforced with poly(L-lactide) (PLLA) or PGA fibers displayed improved mechanical strength and were successfully substituted for the vena cava and pulmonary artery in many animal and clinical trials [18,19]. However, the application of the scaffolds was restricted to low-pressured vessels such as the pulmonary artery or vena cava because of insufficient mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…evaluated the endothelial function and mechanical strength of tissue -engineered vascular autograft s ( TEVA s) constructed with autologous mononuclear BMCs and a P(LA/CL) scaffold using a canine inferior vena cava ( IVC ) model. The mechanical strength change in vitro with time is shown in Figure 14.9 [18] . Figure 14.10 indicates no statistical differences in strength among IVCs of dog (shown as a control) and 6 -and 12 -month TEVAs.…”
Section: Vascular Tissuementioning
confidence: 99%